The effect of non-severe traumatic brain injury on the functional organisation of the default mode network - Rahman, Muhammad Riddha Abdul (2024)
The organisation of the resting-state networks (RSNs) can provide insight into the functional aspects of the brain. The default mode network (DMN), one of the RSNs, is a set of brain regions that are active when the individual is not engaged in a specific task, but rather in a state of rest or introspection. The DMN has been implicated in various cognitive functions, such as memory, self-referential processing, and social cognition. Traumatic brain injury (TBI) is a common cause of neurological impairment that can affect the structure and function of the DMN. However, most studies on the impact of TBI on the DMN have focused on severe or moderate cases, while the effect of non-severe TBI remains unclear. This study explored the longitudinal effects of non-severe TBI on the functional integrity and network organisation of the DMN using functional magnetic resonance imaging (fMRI) and electroencephalography (EEG), as well as neuropsychological assessments and reaction time tasks. All participants underwent resting-state scanning (fMRI: Healthy, n = 20, TBI, n = 20; EEG: Healthy, n = 25, TBI, n = 25), while a subset of the participants was assessed using a neuropsychological battery of tests and reaction time tasks. Additionally, a subset of the participants returned for the second and third time scanning and assessments. All functional data were preprocessed and entered into statistical analysis, while the off-scanning assessments were statistically analysed separately and then entered into correlation analysis with the fMRI functional connectivity. Four nodes of the DMN were analysed for their intra and internetwork functional organisation: the precuneus or posterior cingulate cortex (PCC), medial prefrontal cortex (MPFC), and bilateral inferior parietal lobules (IPL). Within and between-group analyses were conducted to explore the alteration of functional organisation between the healthy and TBI groups. Significant alterations were detected in activation, functional and effective connectivity, global EEG connectivity, neuropsychological performance, and reaction time scores within the TBI groups across time, compared to the healthy control. Evidence of plasticity was also observed, particularly in the six-month time point. Therefore, this study holds significance in elucidating the reorganisation of the DMN following non-severe TBI and its long-term effects on the functional aspect of the brain, both in connectivity and cognitive domains.